2020
DOI: 10.7759/cureus.10805
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking a Psychiatric Disorder: Heroin-Induced Leukoencephalopathy

Abstract: Toxic leukoencephalopathy is a rare cause of encephalopathy. We describe two cases of toxic leukoencephalopathy associated with opiate abuse where they were misdiagnosed and admitted to the psychiatric ward. In our case series, both patients presented with behavioral changes, restlessness, pressured speech, and cognitive impairment for which they were initially labeled as psychiatric patients and were treated as such. However, after an extensive workup to elucidate the etiology of alteration in mental status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…We distinguish 2 forms: the most frequent one being the chronic form typically revealed by insidious manifestations, and the relatively rare and more severe one being the acute form. 1 , 2 Toxic leukoencephalopathy induced by heroin consumption represents a rare entity, described only in its acute form, and that appears to affect almost exclusively the patients who have inhaled the drug. 3 …”
Section: Discussionmentioning
confidence: 99%
“…We distinguish 2 forms: the most frequent one being the chronic form typically revealed by insidious manifestations, and the relatively rare and more severe one being the acute form. 1 , 2 Toxic leukoencephalopathy induced by heroin consumption represents a rare entity, described only in its acute form, and that appears to affect almost exclusively the patients who have inhaled the drug. 3 …”
Section: Discussionmentioning
confidence: 99%
“…There have also been cases reported with abrupt symptom onset, presenting as confusion, behavioural changes, ataxia, stupor and dementia [81]. As a result there have been instances where cases are misdiagnosed as psychiatric patients, and it is likely that this is a common occurrence [82]…”
Section: Clinical Presentations and Underlying Mechanismsmentioning
confidence: 99%
“…There have also been cases reported with abrupt symptom onset, presenting as confusion, behavioural changes, ataxia, stupor and dementia [81]. As a result there have been instances where cases are misdiagnosed as psychiatric patients, and it is likely that this is a common occurrence [82] Movement disorders Myoclonus (quick, involuntary muscle jerks) are known side‐effects of high‐dose opioid analgesics and as a result are often encountered in the palliative care setting. The cause is thought to be neuroexcytotoxicity secondary to an accumulation of several metabolites, such as morphine‐3‐glucuronide or hydromorphone‐3‐glucuronide, rather than due to the opioids themselves [83].…”
Section: Clinical Presentations and Underlying Mechanismsmentioning
confidence: 99%
“…However, recent experimental studies show that drug abuse also chronically modulates the activity of projecting EGP neurons [ 9 , 10 ]. In human research, both postmortem [ 11 13 ] and neuroimaging studies [ 14 16 ] revealed structural abnormalities in the GP in heroin addiction (for a review see: [ 17 ]). The neuronal population in the GP consists mainly of GABAergic projection neurons with long thick dendrites forming a dense fibre network [ 7 , 18 ].…”
Section: Introductionmentioning
confidence: 99%